The Action Mechanism of the Purified Platelet Aggregation Principle of Trimeresurus mucrosquamatus Venom - Ouyang, Chaoho; Teng, Che-Ming (Thrombosis and Haemostasis, 1979)
The minimal concentration of the platelet aggregation principle (Platelet Aggregoserpen- tin, PAS) necessary to induce platelet aggregation was 10 ng/ml, about one-hundredth of that of the crude venom. PAS induced the release of platelet factors 3 and 4 from platelets, but the released platelet factor 3 was easily inactivated by the anti-phospholipid effect of PAS. Pretreatment of platelets with neuraminidase potentiated PAS-induced platelet aggregation. PAS-induced platelet aggregation was independent on released ADP; it could occur in the ADP-removing systems, such as apyrase or a combination of phosphoenolpyruvate and pyruvate kinase. However, PAS-induced platelet aggregation could be inhibited by adenine nucleotides and adenosine.PAS-induced platelet aggregation was inhibited by some anti-inflammatory agents, antimalarial drugs, local anesthetics, antihistamine and smooth muscle relaxants. After deaggregation of PAS-treated platelets, thrombin and sodium arachidonate could further induce platelet aggregation, but ADP and second dose of PAS could not. It is concluded that PAS-induced platelet aggregation is due to prostaglandin synthesis. Recent literatures on the mechanism of platelet aggregation were surveyed and the actions of PAS were discussed.